Remodeling digital marketplace through Metaverse: A multi-path model of consumer neuroticism, parasocial relationships, social media influencers credibility, and ppenness to Metaverse experience - Sanan Waheed Khan; Syed Hassan Raza; Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Metaverse promises new frontiers in mobility, collaboration, and connectedness in a digital universe poised to digitize our world of workplace and marketplace. The current study aims to explore the effect of consumer neuroticism, parasocial relationships, social media influencers' credibility, and openness to Metaverse experience on the intention to use the Metaverse digital marketplace. Prominent theories, including elaboration likelihood model and personality traits notion, supported the development of a multi-path model for the intention to use Metaverse digital marketplace. Drawing on extensive data of social media active users (N=1861) and covariance-based structural equation modeling (CB-SEM), the novel findings revealed that parasocial relationships and social media influencers' credibility positively trigger intentions to use the Metaverse digital marketplace. Moreover, a higher tendency of openness to Metaverse experience intensifies the effect of parasocial relationships on the intentions to use the Metaverse digital marketplace. Interestingly, openness to Metaverse experience is negatively associated with consumers' neuroticism. The study implications offer new insights into parasocial relationships and the credibility of social media influencers in determining followers' intention to use the Metaverse digital marketplace. Transition to the digital marketplace can be accelerated if consumers (prone to neuroticism) are offered professional support to overcome negative emotions (e.g., fear and helplessness) toward emerging digital technologies such as the Metaverse
Keywords: 330; Metaverse; parasocial relationship; social media influencer credibility; consumer neuroticism; elaboration likelihood model; personality traits; and technology acceptance model